2023
DOI: 10.3389/fnut.2023.1188958
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association between vitamin D supplementation and the risk of acute respiratory tract infection in the healthy pediatric group

Abstract: No previous meta-analysis had explored the association between vitamin D supplementation in healthy pediatrics and the risk of acute respiratory tract infections (ARTIs). Thus, we meta-analyzed the current evidence in this regard to provide sufficient knowledge about this risk-benefit ratio for vitamin D supplementation in this specific age group. We searched seven databases for randomized controlled trials (RCTs) that investigated the effect of vitamin D supplementation and ARTIs risk on a healthy pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, a review by Cho and colleagues showed that vitamin D supplementation has no clinical effect in the prevention of ARIs in the main analysis and subgroup analysis of high-quality studies [12], which was consistent with our study. Some reviews also explored the association between vitamin D supplementation in children and the risk of ARIs [13,14,43,44], all of them indicated…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a review by Cho and colleagues showed that vitamin D supplementation has no clinical effect in the prevention of ARIs in the main analysis and subgroup analysis of high-quality studies [12], which was consistent with our study. Some reviews also explored the association between vitamin D supplementation in children and the risk of ARIs [13,14,43,44], all of them indicated…”
Section: Plos Onementioning
confidence: 99%
“…that vitamin D supplementation provided no benefit in preventing ARIs. However, two of these reviews showed high-dose vitamin D might reduce the incidence of influenza in children [13,14]. Another review also suggested that the most effective approach to optimizing and sustaining serum (25(OH)D) concentration throughout the year is by administering a significant bolus dose, followed by monthly or bi-monthly maintenance doses [45].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D‘s potential to enhance innate and adaptive immune responses suggests a promising adjunctive strategy to reduce the incidence and severity of respiratory infections in this vulnerable population [ 15 , 16 , 17 ]. In this context, several large studies and meta-analyses observed the safety and overall protective role of vitamin D supplements and higher 25(OH)D levels against respiratory infections [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have also demonstrated the safety profile of vitamin D supplementation in different populations, even at high-dose daily vitamin D supplementation [ 15 ]. A monthly intake of 300,000 IU of vitamin D3 by hemodialysis patients aged 18 and above for 9 months [ 16 ] and a meta-analysis have demonstrated the safety of pediatric patients aged 0–18 years taking 400 IU/d of vitamin D [ 17 ]. Nevertheless, the dosage levels of vitamin D supplementation vary in clinical practice, and consensus on their comparative efficacy has not been reported yet, making decision-making very difficult.…”
Section: Introductionmentioning
confidence: 99%